Material Hide‐and‐Seek: Looking for the Resource Savings Due to International Trade of Food Products. Issue 7 (27th July 2021) - Dombi, Mihály; Szakály, Zoltán; Kiss, Virág Ágnes; Cao, Zhi; Liu, Gang
Abstract: Adverse environmental effects of international trade are emphasized in the literature frequently. Nevertheless, following a theoretical trade logic, the production of goods in regions with higher resource efficiency may lead to reduced global resource use. In this article, major drivers of food‐related material footprint (MF) are analyzed at the global, regional, and country levels. Changes in consumption, the supply chain's efficiency, and participation in international trade are considered drivers of MF. An index decomposition analysis was conducted to assess the contribution of these factors to the variation of the MF in time. Our results partially prove that the optimization regarding natural resource use may contribute to a lower MF of food consumption. Regions and countries with increasing food imports reinforce their efficiency improvement with the lower resource intensity of imported goods, and the international trade counteracted the effects on additional resource requirements of increasing consumption throughout the analyzed period (1990–2013). Furthermore, the impact of international trade on capital stock is discussed. In line with the descending flow‐type material intensity by approximately 5%, the material composition of the footprint has shifted toward stock building materials. Additionally, the intensity of the trade was found to be negatively correlated with domestic efficiency improvements. Plain Language Summary: Although serious resource needs and pollutions associate the international trade, it is suspected to play an essential role in the more effective distribution of natural resources (e.g., land, water, energy). In this article, significant drivers of food‐related material footprint (MF) are analyzed globally, at regional and country levels. Changes in consumption, the supply chain's efficiency, and participation in international trade are considered to form food products' overall resource requirements. Our results partially prove that the optimization regarding natural resource use may contribute to a lower MF of food consumption. Increasing food imports reinforces efficiency improvement with the lower resource needs of imported goods. The international trade counteracted the effects on additional resource requirements of increasing consumption throughout the analyzed period (1990–2013). It was also described that the more effective the food system becomes, the more resources are used to build up its infrastructure. Key Points: International trade of food products reduced the rise of material footprint in our sample on a global scale A trade‐off between material efficiency improvement and material stock accumulation is detected Domestic efficiency improvements tend to substitute for food imports